Obtenção e aplicação de fotoanodos baseados em TiO2 com adição de nitretos de carbono polimérico do tipo poli(heptazina imida) - Blaskievicz, Sirlon Francisco (Universidade Federal de São Carlos, 2022)
In this work, poly(heptazine imide) carbon nitrides containing metals single atom in the ionic form were evaluated alone and in the combination with TiO2. Initially, a percentage of 2.5% of the nickel-containing material (Ni-PHI) was added to a commercial TiO2 paste and applied to methanol oxidation under solar-simulated radiation and UV light. On a 30-layer film and under UV radiation, the TiO2-Ni-PHI sample obtained a photocurrent response of 11 mA cm-2. The performance improvement with Ni-PHI is probably due to the formation of a heterojunction between TiO2 and PHI, while nickel sites act through a cocatalysis process. In situ measurements allowed to infer that methanol was selectively oxidized to formaldehyde in the dark, and formic acid and CO2 under light. When coating Ni-PHI with a polymer of intrinsic microporosity (PIM-1) there was an intensification of the photocurrent by mechanical stabilization and subsequent re-oxidation of photogenerated H2 in the system. The behavior of Co-PHI, Co-Ni-PHI, and K-PHI was also evaluated, and it was possible to observe that the samples containing transition metals had the potential to be applied both in reduction and oxidation reactions, due to the ease of nox change of the cations used, but the highest photocurrent was obtained by K-PHI, the most conductive and organized sample. In the screening of different percentages of K-PHI to TiO2, it was found that high percentages (above 5%) created charge recombination sites, reducing the performance of the photoanode. The 5% TiO2-K-PHI film had promising results in the oxidation of paraoxon (POX) and its derivative p-nitrophenol (p-NP), where the removal rates of these pollutants increased significantly with the addition of H2O2, and consequently ROS generation, which preferentially favors indirect degradation processes, reaching removal rates of more than 80%. All these results indicate that the photoanodes obtained prove to be interesting alternatives for use in energy generation devices, as well as for chemical detoxification.
Obtention and application of TiO2-based photoanodes with addition of Poly(Heptazine Imide) Carbon nitrides
Keywords: Nitretos de carbono poliméricos; Reação de oxidação de methanol; Oxidação fotoeletroquímica; Single atom catalyst; CIENCIAS EXATAS E DA TERRA::QUIMICA